Evidence-Based Management of Uterine Fibroids With Botanical Drugs-A Review - Arip, Masita; Yap, Vi Lien; Rajagopal, Mogana; Selvaraja, Malarvili; Dharmendra, K; Chinnapan, Sasikala (Frontiers in Pharmacology, 2022)
Uterine fibroid (UF) is a common benign gynecological tumor that affects the majority of women over their lifetime. Several pharmacological agents are available to reduce the size of fibroids and to ameliorate the symptoms of UF. However, these drugs are expensive and usually associated with profound side effects. Thus, at this point herbal products gaining attention in this era due to their cost-effectiveness with a comparable or more potent therapeutic efficacy while demonstrating lesser adverse effects. Hence, the objective of this review is to summarize the available information on the mechanism of various herbs and polyherbal formulation with anti-uterine fibroid activity. A subject search randomly was performed on herbs with anti-uterine fibroid activity using several search engines, which include PubMed, Google Scholar, Science Direct, and other open access journals available online. Based on the literature identified, a total of five herbs and three polyherbal formulations were included and discussed in this review, which yields useful information regarding the mechanism of different herbs and polyherbal formulation in exerting anti-uterine fibroid activity for its potential use as an alternative treatment choice for uterine fibroid.